Extraction and High Purification of Nicotine from Iraqi Tobacco Leaf Formanufacturing, Pharmaceutical, and Medicinal Uses - Husam Alaa Hameed Al-Khinuliu; Essam Fadel Al-wan Al-Jumaili (Indian Journal of Forensic Medicine & Toxicology, 2021)
Bachground: Nicotine is highly addictive plant derived alkaloid and the most important species in humanuse today is Nicotianatabacum. There are direct health effects of chronic nicotine exposure. Even in lowdoses, nicotine causes vasoconstriction and other cardiovascular effects related to catecholamine release andpromote angiogenesis, neuroteratogenicity, and possibly some cancers. Methods: A preliminary investigationto analyze the nicotine contained in Iraqi tobacco leaves was carried out using gas chromatography-massspectrometry (GC-MS). Nicotine is an alkaloid, and alkali methanol and Lipophilic solventsystem methods(LSS) have been extracted and determined by GC-MS from tobacco leaves. Results: The detection limit fornicotine was for non-selective monitoring at the ppm level and for selective detection at the nanogram level.This is a simple method of thin layer chromatography (TLC) and chromatography mass spectrometry (GCMS)for the tobacco leave analysis of nicotine. The final purity of nicotine is 99%. Conclusion :the methodswhich used in this study gave very high purity of nicotineafter converting the crude nicotine to its esters.